Publishing Activities of O.Rusova as the Way to Enlightenment - Reznichenko, Iryna (Pedagogical Discourse, 2013)
Journalistic, editorial and publishing activities of Alexander Alexandrovich Rusova, the famous Ukrainian scientist, ethnographer, folklorist and public figure, have been analyzed on the basis of research of a large number of sources, including little-known archival documents. His participation in the publishing of such periodicals as «Kiev Telegraph», «Work», «Kievan antiquity», «Hutorаnyn», «Ukrainian vesnik», «Country» has been considered. And also the role of A.Rusov in education of Ukrainian people and his contribution to the social and political life of Ukraine has been pointed out.